Movement for change : evangelicals and social transformation - Hilborn, David (Carlisle [England], Paternoster Press, 2004)
This title concerns the Evangelical Alliance (Acute) report.
Keywords: Church and the world; Evangelical perspectives; Evangelicalism.-- Social aspects; Social change.-- Religious aspects; Social transformation